The Influence of Brand Image and Product Quality on Glad2glow Skincare Purchasing Decisions at the Gloria Cosmetic88 Store in Sampit - Bio Ertanto; Hari Susanto; Guruh Fajar Alamsyah; Deky Prasetyo; Melda Rizka Amelia (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The title of this research is The Influence of Brand Image and Product Quality on Glad2glow Skincare Purchasing Decisions at Gloria Cosmetic88 Store in Sampit. This research was conducted in Sampit, East Kotawaringin Regency, Central Kalimantan. This research used Accidental Sampling technique. The data were tested using validity test, reliability test, hypothesis test, and research data analysis using descriptive analysis, multiple linear regression analysis, correlation coefficient analysis and determination analysis. In this research, the data were collected through questionnaire method of 75 respondents, which were distributed to consumers who made purchases at Gloria Cosmetic88 store in Sampit. The results of this study indicate that the t-test of the Brand Image variable (X1) has a calculated t value > t table (6.556 > 1.99394 and a significant level (0.000 < 0.05) so Ho is rejected and Ha is accepted, this means that Brand Image has a significant effect on the Purchase Decision of glad2glow skincare at the Gloria Cosmetic88 store in Sampit. The t-test of the Product Quality variable (X2) has a calculated t value > t table (5.576 > 1.99394) and a significant level (0.00 < 0.05) so Ho is rejected and Ha is accepted, this means that Product Quality has a significant effect on the Purchase Decision of glad2glow skincare at the Gloria Cosmetic88 store in Sampit. While for the f test it is known that f count > ft table (308.476 > 3.13) with a significant level of 0.000 < 0.050 so Ho is rejected and Ha is accepted, meaning that the independent variables are Brand Image (X1), and Product Quality (X2) simultaneously influence the dependent variable, namely the Purchase Decision (Y). While the correlation analysis (r) of 0.946 indicates a very strong correlation between Brand Image and Product Quality on the Purchase Decision of glad2glow skincare at the Gloria Cosmetic88 store in Sampit. While the determination analysis (R2) obtained R2 = 0.895 (89.5%). This reveals that the influence of Brand Image (X1) and Product Quality (X2) influences the Purchase Decision (Y) by 89.5%. While the remaining 10.5% is influenced by other variables not included in this study such as price, promotion, location and so on.